A Study on Obesity in Relation to Socio -Economic Status in Men and Women - Vinod Porwal; Anand Verma; Sameer Inamdar; Pranay Bajpai (Medsci Publications, 2013)
Introduction: Obesity now a day's considered an epidemic earlier was considered a disease of western world, and highly affluent society. But now days it is seen more in low socio economic group also. Objective: To investigate obesity in relation to socio economic status inmen & women in Indians. Methods: We reviewed data from a health check up program of workers at Municipal Corporationworking as sweeperswhich was done at SAIMS Medical CollegeIndore and executives coming for routine health check up. Data was pooled, and was used to compare ratio of obesity and socio economic status. Results: Obesity was observed more in men & women of low socio economic status as compared to high socioeconomic status, and in the same low socioeconomic group it was observed more in women. Conclusion: Higher education and high socio economic status were associated with low risk of obesity in men & women, where as higher occupation status was associated with lower riskof obesity. It has been shown in some studies that the group having low socio economic status had increased risk of obesity.